Dampak Karakteristik Sosiodemografi dan Tingkat Kepatuhan Terapi Antihipertensi Terhadap HRQoL Pasien Gagal Jantung Kongestif - Maryorie Rosa; Armenia Armenia; Dedy Almasdy (Fakultas Farmasi Universitas Andalas, 2015)
Health Realted Qulity Of Life (HRQoL) is the patient perspective to their medication and illnes. The objective of study is to determine the impact of social demography characteristics, and medical adherence to the HRQoL of congestive heart failure patients in M. Djamil Hospital Padang. Data social demography, adherence, and HRQoL of 111 patients were collected by guided interview and completed by their medical record. We used T-test and one-way ANOVA, while 95% confidence intervals was taken for the significance. Patients who completed the education in senior high school possessed the best HRQoL score and the patients with lower level education had a worse HRQoL score (P<0,05). The best HRQoL score was showed by civil servant compared to other professions (P<0,05). While the worse HRQoL performed by the patient who had lower level of medication adherence (P<0,05). While the gender and age of the patients were not significantly affected the HRQoL score (P>0,1).